Asthma Exacerbation in Children: A Practical Review - Lin-Shien Fu; Ming-Chin Tsai (Elsevier, 2014)
Asthma is the most common chronic lower respiratory tract disease in childhood throughout the world. Despite advances in asthma management, acute exacerbations continue to be a major problem in patients and they result in a considerable burden on direct/indirect health care providers. A severe exacerbation occurring within 1 year is an independent risk factor. Respiratory tract viruses have emerged as the most frequent triggers of exacerbations in children. It is becoming increasingly clear that interactions may exist between viruses and other triggers, increasing the likelihood of an exacerbation. In this study, we provide an overview of current knowledge about asthma exacerbations, including its definition, impact on health care providers, and associated factors. Prevention management in intermittent asthma as well as intermittent wheeze in pre-school children and those with persistent asthma are discussed. Our review findings support the importance of controlling persistent asthma, as indicated in current guidelines. In addition, we found that early episodic intervention appeared to be crucial in preventing severe attacks and future exacerbations. Besides the use of medication, timely education after an exacerbation along with a comprehensive plan in follow up is also vitally important.